Bilateral Paraventricular Nucleus Upregulation of Extracellular Superoxide Dismutase Decreases Blood Pressure by Regulation of the NLRP3 and Neurotransmitters in Salt-Induced Hypertensive Rats - Su, Qing; Yu, Xiao-Jing; Wang, Xiao-Min; Li, Hong-Bao; Li, Ying; Bai, Juan; Qi, Jie; Zhang, Nianping; Liu, Kai-Li; Zhang, Yan; Zhu, Guo-Qing; Kang, Yu-Ming (Frontiers in Pharmacology, 2021)
Aims: Long term salt diet induces the oxidative stress in the paraventricular nucleus (PVN) and increases the blood pressure. Extracellular superoxide dismutase (Ec-SOD) is unique antioxidant enzyme that exists extracellular space and plays an essential role on scavenge excessive reactive oxygen species (ROS). However, the underlying mechanism of Ec-SOD in the PVN remains unclear. Methods: Sprague-Dawley rats (150g to 200g) were fed either a high salt diet (80g/kg, HS) or normal salt diet (0.9g/kg, NS) for 6 weeks. Each group of rats were administrated with bilateral PVN microinjection of AAV-Ec-SOD (Ec-SOD overexpression) or AAV-Ctrl for the next 6 weeks. Results: High salt intake not only increased mean arterial blood pressure (MAP) and the plasma noradrenaline (NE), but also elevated the NAD(P)H oxidase activity, the NAD(P)H oxidase components (NOX2 and NOX4) expression, and ROS production in the PVN. Meanwhile, the NOD-like receptor protein 3 (NLRP3)-dependent inflammatory proteins (ASC, pro-cas-1, IL-β, CXCR, CCL2) expression, and the tyrosine hydroxylase (TH) expression in the PVN with high salt diet were higher but the GSH level, Ec-SOD activity, GAD67 expression and GABA level were lower than the NS group. Bilateral PVN microinjection of AAV-Ec-SOD decreased MAP and the plasma NE, reduced NAD(P)H oxidase activity, the NOX2 and NOX4 expression, and ROS production, attenuated (NLRP3)-dependent inflammatory expression and TH, but increased GSH level, Ec-SOD activity, GAD67 expression and GABA level in the PVN compared with high salt group. Conclusion: Excessive salt intake not only activates oxidative stress but also induces the NLRP3-depentment inflammation and breaks the balance between inhibitory and excitability neurotransmitters in the PVN. Ec-SOD, as a essential anti-oxidative enzyme, eliminates the ROS in the PVN and decreases the blood pressure, probably through inhibiting the NLRP3-dependent inflammation and improving the excitatory neurotransmitters release in the PVN in the salt-induced hypertension.